2005
DOI: 10.1086/432621
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Infectious Diseases--Certified Physicians and General Medicine--Certified Physicians in the Level of Comfort with Providing Primary Care to Patients

Abstract: We found that ID-certified physicians and GM-certified physicians at ID clinics reported less comfort prescribing medications for common comorbid conditions, compared with generalist physicians at GM clinics, despite a substantial prevalence of these conditions at the ID clinics. Methods are needed to increase physicians' level of comfort for prescribing treatment and/or to facilitate referral to other physicians for treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 16 publications
1
45
1
Order By: Relevance
“…These results are parallel to an earlier report that found that ID-certified physicians were less comfortable with prescribing medications to their HIV-positive patients for hyperlipidemia, diabetes, hypertension, and depression than GM-certified physicians to their patients. 31 Interventions should also target increased detection of smoking particularly among patients with smoking-related diseases such as chronic obstructive pulmonary disease, coronary artery disease, and bacterial pneumonia who would especially benefit from smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…These results are parallel to an earlier report that found that ID-certified physicians were less comfortable with prescribing medications to their HIV-positive patients for hyperlipidemia, diabetes, hypertension, and depression than GM-certified physicians to their patients. 31 Interventions should also target increased detection of smoking particularly among patients with smoking-related diseases such as chronic obstructive pulmonary disease, coronary artery disease, and bacterial pneumonia who would especially benefit from smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that HIV providers (both infectious disease specialists and general medicine-certified physicians working at infectious disease clinics) are less comfortable treating hyperlipidemia, diabetes, hypertension, and depression compared to providers at general medicine clinics. 22 High-volume and/or over-paneled HIV providers also refer patients for management of these co-morbidities more often and discuss condom use and transmission risk reduction less consistently; 23 such practice patterns likely reflect multiple issues, including time constraints and competing demands, and possibly provider experience and/or comfort. Finally, data suggest that some HIV-infected patients are not receiving routine health maintenance services (e.g., mammography and colorectal cancer screening).…”
Section: Changing Providers: New Responsibilities Impending Shortagesmentioning
confidence: 99%
“…Providers included attending physicians, residents, fellows, physician assistants, and nurse practitioners; ID clinics have no residents. All non-attending physicians and mid-level providers are supervised by attending physicians, who do not differ by sex, race, or duration of practice; however, ID-certified physicians are older than GM-certified physicians 20 . Some ID and GM providers were also VACS investigators, but this study evaluated the standard clinical care provided at participating VA centers.…”
Section: Providersmentioning
confidence: 99%